Effectiveness and therapeutic alliance between face-to-face and online psychological interventions. A longitudinal study - Mercadal, Josep; Coromina, Laia; Cabré, Victor (Frontiers in Psychology, 2025)
BackgroundSince the pandemic, there has been an evident increase in demand for online psychotherapy. There exist studies focusing on the effectiveness of online therapy and identifying the situations in which it may be helpful, but a gap in literature was found on studying the effectiveness and therapeutic alliance of online psychotherapy compared to face-to-face psychotherapy.ObjectiveThe aim of this study is to evaluate the effectiveness and the evolution of therapeutic alliance between face-to-face and online psychological interventions, from the perspective of both therapists and patients. This article aims to be a continuation of the study initiated by Mercadal and Cabré in which, among other conclusions, it was found that the therapeutic alliance in an online intervention was significantly good, although not as good as in a face-to-face intervention.MethodsA total of 187 subjects aged between 18 and 29 years old participated anonymously and voluntarily in the study, 81 (43.3%), of whom were men and 106 (56.7%) were women. The instruments used were socio-demographic data, the patient version of SOFTA-o (System for Observing Family Therapeutic Alliances-observational), CORE-OM (Clinical Outcomes in Routine Evaluation-Outcome Measure), and HoNOS (The Health of the Nation Outcome Scales).ResultsThe results show that there is more preference for the in-person modality than online. A correlation is also observed between CORE-Om pre and HoNOS pre; and CORE-OM post and HoNOS post, which indicates agreement between patient and therapist regarding the evolution of the treatment. At the same time, patients and therapists report better results in person than online (d = 0.76 and d = 0.91, respectively).ConclusionTherapists perceive a greater improvement after the treatment rather than do patients. In addition, post-treatment scores showing an improvement in the symptomatology are related to a greater Therapeutic Alliance after treatment. Concerning the main aim of this article, both patients and therapists reported that face-to-face therapy obtains better results than the online modality, a finding consistent with the authors’ preliminary studies. However, there are some limitations, such as self-selection of modality by participants, the use of a single therapist, the sample of university students, and the lack of post-intervention follow-up.